Development of a Robotic Arm Platform With Interchangeable Sensors for Remote Inspection of Industrial Plants - Yi, E.C.; Jara, J.; Rivadeneira, F.; Zinanyuca, M.; Cuellar, F. (Institute of Electrical and Electronics Engineers, 2024)
The industrial plant of the Oil&Gas and energy sector requires frequent inspection, digitization, and diagnosis of its critical infrastructure, this is in order to guarantee the safety of people, the environment, and critical assets. In this context, we propose a 6DOF articulated robot arm that is able to perform the inspection tasks autonomously. The robot has interchangeable sensors and a vision system for visual inspection of critical components in the plant such as gauges, pumps, pipes, etc. in industrial settings, aiding in data gathering using YOLO V8 architecture. During the tests, the robotic arm platform was implemented, and were able to pick and place their sensors. Finally, using the YOLO V8 model, it was possible to automatically detect gauges with an Fl-Score of 87.72 % using Adamax optimizer and an IoU threshold of 0.9.
Keywords: Robotic arm; Autonomous inspection; YOLO V8; https://purl.org/pe-repo/ocde/ford#2.03.01